(untitled) (Baghdad Science Journal, 2017)
This study is conducted to determine the effect of pathogenicity of the fungus Lecanicillium lecanii in some aspects of life of the insect saw toothed beetle Oryzaephilus surinamensis L. (Coleoptera: Silvanidae) under laboratory conditions with three concentrations of spores and mildew commentator (1 × 103, 1 × 105, 1 × 107) spore / ml , on eggs and larvae second phase of the insect .The study also includs the effect of the fungus concentrations of germination on rice (jasmine) by using direct spray treatment. The results show great fungus efficiency in the control of some aspects of life of the insect, where varied efficiency depends on the concentration of spores, The highest percentage loss of eggs is 63.33% at a concentration of 1 × 107 spore / m followed by aconcentration of 1 × 105 spore / ml in which the loss is 60 % , while the 50% was at a concentration of 1 × 103 spore / ml, which them decreased to 3.33% at the control treatment .The highest rate of destruction of the larvae of the second phase was 60% at a concentration of 1 × 103 spore / ml , and decreased to 56.66% and 46.66% at concentrations 1 × 107 and 1 × 105 spore / ml respectively. In addition there were no significant differences in germination rates for grain treatment direct spray concentrations of innate commentator.